Elements of discussion about company Petrobras and Political Ecology in the context of creative destruction - Salazar Salgado, Carlos Eduardo (Geografares, 2024)
Political Ecology has, from our perspective, imposed itself as an urgent agenda in reflections regarding the development of productive forces and the destiny of humanity. Our research focuses on Petrobras, and at this time when the discussion of decarbonization of the energy matrix seems to be unanimous in the hegemonic public debate, we make an effort here to reflect on the history of development of environmental standardization and the paths through which the Oil industry is going. The constraints created by new environmental standards have been around since the 1980s and impose technical transformations on the Oil industry which, through creative destruction, expands its surplus producing capacity. Petrobras, as part of a sovereign nation’s project, can play a role in driving changes in the country’s energy matrix, or it can simply continue as a source of capital accumulation and polluting and degrading activity in the territory.